Digital printing systems and office papers interactions and the effects on print quality - KURT, MUSTAFA BATUHAN (My University, 2022)
In this study, electrophotographic printing and inkjet printing systems were applied to some commercial A4 office papers and their effects on print quality were determined. It is to evaluate the print quality by determining the test parameters that measure the print quality by applying electrophotographic printing and inkjet printing systems to some commercial office papers that have determined the surface properties and optical properties supplied from the market. Print quality was measured by testing with parameters such as delta gloss 60 degrees, print lightness, print chroma, print density. As a result of the tests determined for print quality; print density values were low in A4 office papers with high roughness and porosity values, and the specular gloss values of the samples decreased in both printing applications. In electrophotographic printing; it was determined that darker colors formed with print lightness parameter, and the color scale increases in two-sided printing with print chroma values. It was determined that the color scale of print chroma values increased in two-sided prints. It was determined that mostly some commercial office papers were positively affected by printing on one side in inkjet printing and by printing on two-sided in electrophotographic printing.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KAĞIT & AHŞAP; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, PAPER & WOOD; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; electrophotography; inkjet; office papers; print quality; printing